2021
DOI: 10.7717/peerj.11400
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney disease in hospitalized acute kidney injury patients

Abstract: Background Acute kidney injury (AKI) and chronic kidney disease (CKD) have become worldwide public health problems, but little information is known about the epidemiology of acute kidney disease (AKD)—a state in between AKI and CKD. We aimed to explore the incidence and outcomes of hospitalized patients with AKD after AKI, and investigate the prognostic value of AKD in predicting 30-day and one-year adverse outcomes. Methods A total of 2,55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…First, we depicted the clinical course of AKI – AKD – MAKE30 – 90-day adverse outcomes, aiming to provide information on the renal function progression after AKI in pediatric patients. We found that a further progression of renal injury after AKI could add the risk of 30- and 90-day adverse outcomes, which supported the results of our previous study of AKD in hospitalized adult patients with AKI ( 8 ). AKI stage 2–3, which was generally considered to be associated with increased risks of CKD, kidney failure, and mortality ( 1 , 16 18 ), was no longer a predictor for adverse outcomes in our multivariable logistic regression analysis.…”
Section: Discussionsupporting
confidence: 91%
“…First, we depicted the clinical course of AKI – AKD – MAKE30 – 90-day adverse outcomes, aiming to provide information on the renal function progression after AKI in pediatric patients. We found that a further progression of renal injury after AKI could add the risk of 30- and 90-day adverse outcomes, which supported the results of our previous study of AKD in hospitalized adult patients with AKI ( 8 ). AKI stage 2–3, which was generally considered to be associated with increased risks of CKD, kidney failure, and mortality ( 1 , 16 18 ), was no longer a predictor for adverse outcomes in our multivariable logistic regression analysis.…”
Section: Discussionsupporting
confidence: 91%
“…Given the heterogeneous and multifactor etiology of ischemic AKI, the incidence estimates vary widely among different patient-related risk factors. The incidence of AKI in hospitalized patients is 11.6-23.9% (8,9), while the incidence of ischemic AKI of overall AKI patients is range from 55.6 to 77.8% (14)(15)(16)26), approximately. In our study, the incidence of ischemic AKI among hospitalized patients is 5.3% and 71.8% in overall AKI patients, demonstrating ischemic AKI common among hospitalized AKI patients.…”
Section: Discussionmentioning
confidence: 99%
“…When AKI occurred in COVID-19 positive patients, the proportion of death could be as high as 50% (12). Not surprisingly, some reports showed that prerenal AKI [one form of ischemic AKI (13)] accounted for more than half of the hospitalized AKI patients (14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The model displayed good predictive power with an AUROC of 0.834 (95% CI:0.773-0.895) in the training dataset and an AUROC of 0.851 (95% CI:0.753-0949) in the validation dataset. Yan et al also established a prediction model using multivariable logistic regression analysis (37). The 8-variable model showed good discrimination and calibration in predicting AKD stage 2-3 with the AUROC being 0.85 (95% CI:0.83-0.87).…”
Section: Discussionmentioning
confidence: 99%